Kemampuan Deteksi Birahi dan Penentuan Waktu Kawin Sapi Bali Setelah Partus Di Kecamatan Taniwel Timur Kabupaten Seram Bagian Barat - Tarigan, Delvia Br; Siwa, Isak P; Labetubun, Jusak (Universitas Pattimura, 2024)
The aim of this research was to determine the ability to detect lust and determine the correct mating time by farmer-breeder respondents in East Taniwel District, West Seram Regency. The research method is a survey method and the sample villages and respondents are determined based on the purposive sampling method. The variables observed consisted of: the ability to detect lust, determining the time of mating after parturition and maternal productivity (including; age at first marriage, pregnancy rate, birth rate, postpartum mating and pre-weaning child deaths. The results showed that 86.66% of respondents were farmer farmers in East Taniwel District has the knowledge, ability and skills in detecting postpartum heat in the medium category (able to name 2-3 categories) and 100% do not have the knowledge and ability in determining the right mating time after parturition. The potential productivity of Bali cows is age first mating 18.2 ± 1.16, pregnancy rate 88.01%, birth rate 98.85%, postpartum mating 4.8 ± 0.8, and pre-weaning mortality 8.90%.